How Representative are Representative Workers? An Assessment of the Hypothetical Workers Commonly Used in Social Security Studies - Pfau, Wade D. (Journal of Income Distribution®, 2009)
An understanding of the financial and distributional consequences of Social Security reform requires knowledge about the actual life circumstances of participants, including the level and pattern of their lifetime earnings and their age at retirement. Some analyses of Social Security reform make simplifying assumptions about these characteristics by using ‘hypothetical workers’ with set career paths. We seek to develop greater understanding about actual lifetime earnings patterns to compare with hypothetical workers and find discrepancies which lead typical hypothetical workers to produce a more favorable impression for defined-contribution pension reforms. We suggest modifications to make a more suitable hypothetical worker.